![\because3x^3+6x^2+3x](https://img.qammunity.org/2023/formulas/mathematics/college/ln5gxjohppquolmvu70gztujw1bkyqvuz7.png)
→ To factorize it we must find the greatest common factor of the 3 terms
∵ The common factor of 3, 6, and 3 is 3
∵ The common factor of x^3, x^2, and x is x
∴ The greatest common factor of the 3 terms is 3x
→ Divide each term by 3x
![\because(3x^3)/(3x)=x^2](https://img.qammunity.org/2023/formulas/mathematics/college/ygepjc2sdabx3chmtqaou91mll26mnc931.png)
![\because(6x^2)/(3x)=2x](https://img.qammunity.org/2023/formulas/mathematics/college/387h6koobsvk176pphffb1mh6bhkep2405.png)
![\because(3x)/(3x)=1](https://img.qammunity.org/2023/formulas/mathematics/college/lqo00v0xxzswqh3v9iubmw40u9randm7qg.png)
![\therefore3x^3+6x^2+3x=3x(x^2+2x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/lgexq5jy3l5sk3w8y1dsq3f0qfs0iobe42.png)
→ Now we must factorize the bracket into two factors
![\begin{gathered} \because x^2=x* x \\ \because1=1*1 \\ \because(x)(1)+(x)(1)=2x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v2a8etsy363xvu9xa7xtd6eiispf2rn9bp.png)
![\therefore x^2+2x+1=(x+1)(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/k5msogeqtui2j8ifit9fnozsivg0zmsk9x.png)
∴ The complete factorization is
![3x^3+6x^2+3x=3x(x+1)(x+1)=3x(x+1)^2](https://img.qammunity.org/2023/formulas/mathematics/college/l68f5for3zybq1ecvj3xjqr31y535gvo01.png)